Cortical excitability and sleep deprivation: a transcranial magnetic stimulation study. Issue 6 (1st December 2001) - Civardi, C; Boccagni, C; Vicentini, R; Bolamperti, L; Tarletti, R; Varrasi, C; Monaco, F; Cantello, R
Abstract : The objective was to assess the changes in cortical excitability after sleep deprivation in normal subjects. Sleep deprivation activates EEG epileptiform activity in an unknown way. Transcranial magnetic stimulation (TMS) can inform on the excitability of the primary motor cortex. Eight healthy subjects (four men and four women) were studied. Transcranial magnetic stimulation (single and paired) was performed by a focal coil over the primary motor cortex, at the "hot spot" for the right first dorsal interosseous muscle. The following motor evoked potential features were measured: ( a ) active and resting threshold to stimulation; ( b ) duration of the silent period; ( c ) amount of intracortical inhibition on paired TMS at the interstimulus intervals of 2 and 3 ms and amount of facilitation at interstimulus intervals of 14 and 16 ms. The whole TMS session was repeated after a sleep deprivation of at least 24 hours. After the sleep deprivation, the threshold to stimulation (in the active and resting muscle), as well as the silent period, did not change significantly. By contrast, the paired stimulus study showed a significant (p<0.05) reduction in both intracortical inhibition and facilitation. Thus, TMS showed that sleep deprivation is associated with changes in inhibition-facilitation balance in the primary motor cortex of normal subjects. These changes might have a link with the background factors of the "activating" effects of sleep deprivation.